Class IV laser therapy as treatment for chemotherapy‐induced oral mucositis in onco‐haematological paediatric patients: a prospective study. Issue 6 (25th December 2013) - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A.; Verzegnassi, Federico; Treister, Nathaniel S.; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena
<x xml:space="preserve">Abstract</x> Background Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). Aim This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. Design Eighteen onco‐haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re‐evaluated 11 days after the first day of laser therapy. Results All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11‐day follow‐up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1–2 days of laser therapy. Conclusions Given class IV laser therapy appears to be safe, non‐invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.